Morphological characterization of NERICA mutant lines and their parents - Rana, Md Masud; Islam, Md Ashraful; Imran, Shahin; Rubani, Silve; Hassan, Lutful (Asian Journal of Medical and Biological Research, 2018)
A total of 10 NERICA lines (7 mutants along with 3 parents) of advanced generations were used for morphological and molecular characterization. The experiments were conducted in both Aus and Aman season, 2014 under different field conditions at the field of Biotechnology division, BINA, BAU Campus, Mymensingh-2202 following Randomized Complete Block Design (RCBD) with three replications. The genotypes differed significantly for all the traits. The seasonal differences on all the traits except 100-seed weight were also highly significant. The season’s × genotypes interactions were highly significant. The mean value of days to maturity was the lowest in Aman season than Aus season and the mean yield of rice lines was the highest in Aman season than Aus season. The phenotypic co-efficient of variations (PCV) were higher than genotypic co-efficient of variations (GCV) for all the traits studied indicating that they all interacted with the environment to some extent. All the traits studied expressed moderate to high heritability estimates ranging from 53.70 to 99.54%. High heritability along with high genetic advance was noticed for the traits, number of filled grain panicle-1, number of unfilled grain panicle-1 and plant height. Significant positive correlations were recorded for yield plot-1 with effective tillers hill-1 and panicle length and significant negative correlations were recorded for yield plot-1 with days to maturity and unfilled grains panicle-1. Plant height, total tillers hill-1, effective tillers hill-1, panicle length, filled grains panicle-1 and 100-seed weight showed direct positive effect on yield plot-1 at both genotypic and phenotypic level. Therefore, these characters would be reliable criteria for improving yield. Asian J. Med. Biol. Res. June 2018, 4(2): 207-221